2005
DOI: 10.1128/jcm.43.8.4191-4193.2005
|View full text |Cite
|
Sign up to set email alerts
|

Partial Excision of the Chromosomal Cassette Containing the Methicillin Resistance Determinant Results in Methicillin-SusceptibleStaphylococcus aureus

Abstract: We report a detailed characterization of methicillin-susceptible Staphylococcus aureus isolates from five French hospitals negative for both the mecA and the ccrAB loci but positive for the IS431::pUB110::IS431::dcs structure, present in some Staphylococcus cassette chromosome mec (SCCmec) types. The presence of SCCmecassociated elements suggests that this unusual resistant phenotype is due to a partial excision of SCCmec from epidemic methicillin-resistant S. aureus. The hypothesis of a genetic relatedness is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
48
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 27 publications
4
48
0
2
Order By: Relevance
“…The outbreak strain differs from USA300 MRSA only by an approximately 30-kb deletion consistent with loss of SCCmec IV. Our isolate is similar to USA300 MSSA strains previously described in nonoutbreak-associated settings (3,10,13).…”
supporting
confidence: 50%
“…The outbreak strain differs from USA300 MRSA only by an approximately 30-kb deletion consistent with loss of SCCmec IV. Our isolate is similar to USA300 MSSA strains previously described in nonoutbreak-associated settings (3,10,13).…”
supporting
confidence: 50%
“…In the latter case, some elements are left behind at the ISS. Partial excision of SCCmec from the chromosome of a HA-MRSA strain may result in MSSA with a retained resistance to antibiotics other than β-lactam antibiotics [75]. This phenomenon has previously been described in studies where a high proportion of the investigated MSSA isolates were considered to derive from MRSA with partial excision of SCCmec [76][77].…”
Section: Sccmecmentioning
confidence: 89%
“…Baddour (2007) confirmed in his study that MSRA strains have been implicated in serious infections and nosocomial infectious, the strains being detected with several conventional methods. Following the affirmation that MRSA is considered the main cause of nosocomial infections prevalence, Donnio (2005) demonstrated that in French hospitals, MRSA strains increased until that time of the study. As well as Dickinson (2000) confirmed that Staphylococcus aureus clinical isolates tend to be either very susceptible or very resistant to methicillin.…”
Section: Clinical Isolatesmentioning
confidence: 99%
“…Accessory genome or dispensable genetic material of staphylococci bacteria contains virulence factors such as chromosomal cassettes (Donnio et al, 2005), pathogenicity islands (Che et al, 2014), genomic islands (Juhas et al, 2008), bacteriophages (Orlova, 2012), plasmids and transposons (Bennet, 2008). These contain the responsible genes for resistance to antibiotics, like mecA gene which is responsible for resistance to methicillin (Singh et al, 2006;Ferry et al, 2009).…”
Section: Clinical Isolatesmentioning
confidence: 99%
See 1 more Smart Citation